Peningkatan Kompetensi Staf Tata Usaha melalui Pelatihan EMIS di Satuan Pendidikan Muadalah (SPM) Al-Mashduqiah Kraksaan - Arifin, Misbahul; Qomariatul Jannah, Ulfa (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2025)
Accurate and sustainable data management is a critical requirement for Satuan Pendidikan Muadalah (SPM) in meeting national education reporting standards through the Education Management Information System (EMIS). In practice, limited digital literacy and technical competence among administrative staff often hinder effective EMIS implementation. This community service program aims to strengthen the administrative capacity of SPM Al-Mashduqiah Kraksaan through a structured and need-based EMIS training initiative. The program was implemented using a participatory empowerment approach, actively involving partners in problem identification, training implementation, and evaluation. Data were collected through observation, interviews, and documentation to capture changes in staff competence and institutional readiness. The results demonstrate a substantial improvement in administrative staff skills, particularly in data entry accuracy, validation, and independent system management. In addition, the program produced an EMIS Standard Operating Procedure (SOP) as a sustainable institutional output. Overall, this initiative contributes to strengthening institutional capacity, improving digital data governance, and enhancing the readiness of Islamic educational institutions to support ongoing digital transformation policies